The global impact of the General Data Protection Regulation: implications, challenges, and future outlook in oncology clinical research sponsors - Liu, Xiao; Lacombe, Denis; Lejeune, Stephane (Chinese clinical oncology, 2025)
Oncology clinical trial involves processing of vast amounts of personal health data, including medical history, treatment, biomarker, genetic information, etc., much of which qualifies as special category data under the General Data Protection Regulation (GDPR). While it sought to harmonize the data protection standards across the European Union (EU), its implementation has a profound impact on the operational and regulatory practice for oncology clinical trial sponsors. Its interaction with the Clinical Trials Regulation (CTR), diverse national health data laws, and emerging data localization mandates has made privacy compliance in multi-country clinical trials exceptionally complex for both EU and non-EU sponsors. This narrative review examines how core GDPR principles and requirements play out in the context of oncology clinical trials in the EU, and where tensions arise with CTR obligations and real-world operations. We highlight recurrent challenges in practice, including the need to distinguish ethical consent from GDPR legal bases, to honour data subject rights without unblinding, and to ensure proportionate data collection as study endpoints evolve. Additional difficulties arise from managing biospecimen storage and secondary use, addressing long retention horizons, navigating Member State and intra‑state variations in ethics committee and data protection officer expectations, and overcoming localization barriers that hinder cross-border pooling of rare molecular-marker data. With the evolving complex privacy compliance landscape in EU and beyond, full compliance with all privacy requirements becomes unrealistic for the oncology clinical trial sponsors. Instead of seeking perfection in compliance, which is not the main mission for oncology clinical trials, sponsors should adopt a risk-based approach to prioritize the mitigation of the most significant risks. Drawing on the recurrent challenges identified in this narrative review, we propose such an approach that begins with early scoping of the study type, distinguishing CTR-governed investigational medicinal product trials from other designs, and mapping member state legal bases alongside layered transparency materials. It also involves implementing site-mediated subject rights workflows, carefully justifying the inclusion of "buffer" variables or biospecimens, and planning differentiated retention strategies for samples and data. Sponsors should further incorporate privacy-by-design through country-specific mapping and, where cross-border transfers are constrained, consider federated or "data-visiting" analytics. At the system level, we recommend adopting modular consent language, clarifying controller and processor roles through guidance, maintaining public registers of national derogations, and investing in federated infrastructures and accredited biobanks. These insights aim to help oncology sponsors, as well as other clinical sponsors, ethics committees, privacy professionals, and collaborators, to navigate privacy requirements while continuing to advance clinical trials.